2014
DOI: 10.1155/2014/717318
|View full text |Cite
|
Sign up to set email alerts
|

Serum and Urinary NGAL in Septic Newborns

Abstract: Neutrophil gelatinase-associated lipocalin (NGAL) is postulated to be a potentially new and highly specific/sensitive marker of acute kidney injury (AKI). The aim of this study was to assess the impact of inflammation on serum and urine NGAL in newborns that were treated due to infection. We determined serum and urine NGAL concentrations in 73 infants (51 with sepsis; 22 with severe sepsis) admitted to the Intensive Care Unit in the first month of life, for three consecutive days during the course of treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
29
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 29 publications
7
29
1
3
Order By: Relevance
“…We showed a strong correlation between inflammatory markers such as CRP and PCT and lipocalin-2 assessed both in urine and serum. Similar results were previously obtained in term newborns by us 24 and other researchers. 22,23,25 In our project, sNGAL and uNGAL values were checked as a surrogate, hence possibly more sensitive parameter of kidney injury.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We showed a strong correlation between inflammatory markers such as CRP and PCT and lipocalin-2 assessed both in urine and serum. Similar results were previously obtained in term newborns by us 24 and other researchers. 22,23,25 In our project, sNGAL and uNGAL values were checked as a surrogate, hence possibly more sensitive parameter of kidney injury.…”
Section: Discussionsupporting
confidence: 92%
“…In our opinion it is too soon to relay on s/uNGAL values solely in early recognition of AKI, but we definitely should not neglect this marker. Inflammatory conditions such as BPD 10 and sepsis, and especially urinary tract infection 24,27 are probably the most important limitation for the interpretation of NGAL values, decreasing its specificity in the diagnosis of AKI. However this does not diminish uNGAL value in detection of AKI of non-septic origin in premature infants.…”
Section: Discussionmentioning
confidence: 99%
“…Prior literature has shown that in premature infants without AKI, urine proteins will be highest among those with the lowest GA, probably because of the passive loss of proteins in the context of immature tubular function (6)(7)(8). Previously, we (7) and others (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) have published data on the ability of urine biomarkers to predict AKI in neonates; however, these studies are limited by the size of the cohort or the use of nested case-control methods, with most of these studies evaluating only one biomarker. In addition, previous studies were subject to risk of misclassification bias, given that many infants had only a few SCr levels measured to determine AKI.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 In our study, ten patients (11.4%) did not progress beyond the AKIN stage II, indicating that some patients in this group probably had functional renal failure (transient AKI or prerenal azotemia) without any significant renal tubular injury. The incidence of transient AKI was similar to the study done by Hoste et al 27 (18%).…”
mentioning
confidence: 54%